An Evaluation on "The Literature of the Nafs" in Mawardi's Work Named Kitab Aadab al-Dunya w'al-Din - Kerimoğlu, Özkan (Fırat University, 2024)
In the sacred texts, human beings are described as being created in the most beautiful way. In order to understand and define its integrity of existence in the most accurate way, it is necessary to know both its biological and spiritual aspects. In addition to the well-known and generally accepted characteristics of humans such as will and responsibility, there are also basic realities that constitute humans such as nafs, soul and mind. One of the most powerful factors that make a person virtuous or worthless both in the presence of the Creator and in the eyes of people is the nafs. The nafs has many different meanings such as ”the essence of man, soul, person, self-being, mind, life, lust, desire, the source of bad habits".Philosophers, Sufis and theological scholars with different philosophical ideas in different periods in the history of thought have discussed and evaluated the subject of the nafs. Pythagoras considered the nafs as a substance separate from the body, Democritus as fire or heat, Plato as a substance that gives movement to the body. Aristotle, on the other hand, pointed out the difficulty of defining the soul and talked about three types of the nafs: vegetative, animal and human. The concept of nafs, on whose definition philosophers cannot agree, has a strategic importance as it is accepted as the point of separation of good and evil in religious literature. Because the human nafs, by its nature, has a structure that is prone to worldly pleasures, human desires, wishs and passions. Likewise, human beings are creatures of will, and thanks to this feature, they have the ability and freedom to establish positive and negative relationships and evaluate the beings and events around them. What should be the attitude of a person who has these characteristics towards pleasures, desires and passions? The main theme of our study is Mawardi's answer to this question and the solutions he identified. It was stated that having will makes humans different and superior to other living creatures. In this context, what is expected from a person is to use his will to control his nafs by displaying a sensitive, conscious and astute attitude towards the desires of his soul. It is observed in real life that failure to control one's nafs creates undesirable consequences both individually and socially. If the nafs cannot be controlled consciously, a person may become a victim of excessive passion for the world and the things in it. It is possible for humans to become arrogant and proud and to corrupt the environment, society and the world and make it uninhabitable as a result of pursuing their desires. Therefore, there is a need for a constantly dynamic and active consciousness regarding this feature of the nafs. There is no positive situation that an uncontrollable, undisciplined nafs that is a slave to its desires and passions will bring to its owner. The undisciplined and uncontrolled nafs causes individual, religious, moral and social traumas such as taqiyya, insincere words and actions, formal religious attitudes and behaviors, and alienating others for simple, primitive reasons. This is the point that the thinker focuses on and draws attention to. If a person can manage to control and discipline the passions and desires of his nafs by using his will, space will be opened for virtues that will bring happiness to individual and social life, such as brotherhood, solidarity, altruism. Mawardi evaluated this issue in the fifth chapter of his work Edebü'd-Dünyâ ved-Dîn. Mawardi, who thinks that education is an important factor in the reformation of the nafs, says that the mind and revealed knowledge given to man by God are indispensable elements of this struggle. Because he thinks that the alliance of reason, revelation and knowledge is necessary in distinguishing between right and wrong and in being patient with the harmful and evil tendencies of the nafs. A person who takes revelation, reason, knowledge and wisdom as a guide and whose emotions, thoughts and behaviors are shaped by this guide will not be defeated by his nafs. For this reason, Maverdi emphasizes especially when evaluating the subject of “Literary of the soul” that a person needs decency in adulthood as well as in childhood. In this context, he identified issues such as arrogance, pride, false envy and wrath, which he thought could hinder the evolution of virtue and virtue in individual and social life, and also showed the reasons for these and how to combat them.

Kutsal metinlerde insan, en güzel şekilde yaratıldığı bildirilen bir varlıktır. Onun varlık bütünlüğünü en doğru şekilde anlayıp tanımlayabilmek için biyolojik ve ruhsal her iki yönünü de bilmek gerekmektedir. İnsanın irade, sorumluluk gibi bilinen ve genel olarak kabul gören özelliklerinin yanında nefis, ruh ve akıl gibi insanı oluşturan temel gerçeklikler de söz konusudur. İnsanı gerek Yaratıcının huzurunda gerekse insanlar nazarında erdemli ya da değersiz kılan en güçlü etkenlerden birisi de nefistir. Nefis, “insanın özü, ruh, zat, öz varlık, zihin, hayat, şehvet, istek, kötü huyların kaynağı” gibi çok farklı anlamlara gelmektedir. Düşünce tarihinde farklı dönemlerde farklı felsefi fikirlere sahip filozof, mutasavvıf ve kelam bilgini nefis konusunu ele alıp değerlendirmiştir. Pisagor, nefsi bedenden ayrı bir cevher, Demokritos, ateş veya sıcaklık, Eflatun, bedene hareket veren bir cevher olarak kabul etmiştir. Aristo ise nefsin tanımını yapmanın zorluğuna dikkat çekerek nebati, hayvani ve insani olmak üzere nefsin üç çeşidinden söz etmiştir. Tanımı üzerinde düşünürlerin ittifak edemediği nefis kavramı dini literatürde iyi ve kötünün ayrışma noktası olarak kabul edildiği için stratejik bir öneme sahiptir. Çünkü insan nefsi, doğası gereği dünyevi hazlara, beşeri arzu, istek ve ihtiraslara eğilimli bir yapıya sahiptir. Aynı şekilde insan irade sahibi olan bir varlıktır ve bu özelliği sayesinde çevresindeki varlıklar ve olaylarla ilgili müspet-menfi ilişki kurup değerlendirme yapabilme kabiliyet ve özgürlüğü vardır. Bu özellikleri zatında barındıran insanın, hazlar, istekler ve ihtiraslar karşısındaki tutumu nasıl olmalıdır? Çalışmamızın ana temasını Mâverdî’nin bu soruya verdiği cevap ve tespit ettiği çözüm yolları oluşturmaktadır. İrade sahibi olmanın insanı diğer canlılardan farklı ve üstün kıldığı belirtilmişti. Bu bağlamda insandan beklenen nefsin arzuları konusunda hassas, bilinçli ve dirayetli bir tavır sergileyerek iradesini, nefsini kontrol etmek amacıyla kullanmasıdır. Nefsin kontrol edilememesinin bireysel ve toplumsal açıdan istenmeyen sonuçlar doğurduğu reel hayatta gözlemlenmektedir. Nefsin bilinçli bir şekilde kontrol edilememesi halinde, insan, dünya ve içindekilere karşı taşıdığı aşırı ihtirasın kurbanı olabilir. İnsanın kibir ve gurura kapılarak, arzularının peşinden sürüklenmesi sonucu çevreyi, toplumu ve dünyayı ifsat ederek yaşanmaz hale getirmesi imkân dâhilindedir. Bu yüzden nefsin söz konusu özelliği karşısında sürekli dinamik ve etkin bir bilince ihtiyaç vardır. Arzu ve ihtiraslarının esiri olmuş, kontrol edilemeyen, disiplinsiz bir nefsin sahibine kazandıracağı müspet bir durumdan söz edilemez. Disiplinsiz ve kontrol edilemeyen nefis, takiyyeye, samimiyetsiz söz ve eylemlere, şekli dinsel tutum ve davranışlara, basit, ilkel gerekçelerle başkasını ötekileştirme gibi bireysel, dini, ahlaki ve sosyal travmalara neden olmaktadır. Düşünürün de odaklandığı ve dikkat çektiği husus burasıdır. İnsan, iradesini kullanarak nefsinin ihtiraslarını, arzularını kontrol ve disipline etmeyi başarabilirse, kardeşlik, yardımlaşma, dayanışma, diğerkâmlık gibi bireysel ve toplumsal yaşama mutluluk getirecek erdemlere alan açılmış olur. Mâverdî, Edebü’d-Dünyâ ved-Dîn eserinin beşinci bölümünde bu konuyu değerlendirmiştir. Nefsin ıslah edilmesinde eğitimin önemli bir faktör olduğunu düşünen Mâverdî, Allah tarafından insana verilen aklın ve vahyi bilginin bu mücadelenin olmazsa olmaz unsurları olduğunu söylemektedir. Çünkü o, doğru ile yanlışın ayırt edilmesinde, nefsin zararlı ve kötü eğilimlerine sabredilmesinde akıl, vahiy ve bilgi ittifakının gerekli olduğu düşüncesindedir. Kendisine vahyi, aklı, bilgi ve hikmeti kılavuz edinmiş, duygu, düşünce ve davranışlarını bu kılavuzun şekillendirdiği kişi nefsine yenilmeyecektir. Bu yüzden Mâverdî, “Nefsin edebi” konusunu değerlendirirken insanın, çocuklukta olduğu gibi yetişkinliğinde de terbiyeye ihtiyaç duyduğunu özellikle vurgulamaktadır. Bu bağlamda bireysel ve sosyal hayatta erdem ve faziletin tekâmülüne engel olabileceğini düşündüğü kibir, gurur, yalan haset, gazap gibi hususları belirlemiş, bunların sebeplerini ve bunlarla nasıl mücadele edileceğini de göstermiştir.
Mâverdî’nin Edebü’d-Dünyâ Ve’d-Dîn Adlı Eserinde “Nefsin Edebi” Üzerine Bir Değerlendirme
Keywords: Islamic Philosophy; İslam Felsefesi